Pengembangan Pembelajaran Matematika Berbasis Al Qur'an Di Sekolah Menengah Pertama Muhammadiyah 9 Gemuh Pondok Pesantren Darul Arqam 4 Kendal - Saksono, Deky Yudha; , Prof. Dr. Sutama, M. Pd; , Dr. Samino, M.M (2015)
This study aims to: (1) describe the learning management conducted in the School of Mathematics SMP Muhammadiyah 9 Gemuh Pondok Pesantren Darul Arqam 4 Kendal, (2) describe the development of learning mathematics in the School-Based Qur'an SMP Muhammadiyah 9 Gemuh Pondok Pesantren Darul Arqam 4 Kendal, (3) examined the implementation of learning mathematics in the School-Based Qur'an SMP Muhammadiyah 9 Gemuh Pondok Pesantren Darul Arqam 4 Kendal. Research using the Research and Development to carry out the three steps in the process of research and development: (1) preliminary study consisting of: literature studies, field surveys and drafting models; (2) limited trial; (3) testing of products and the dissemination of results. Data collection techniques using triangulation techniques. Data analysis technique performed on the data that has been collected, the results of the method of documentation, participant observation, interviews, tests. Results of this study (1) The management of learning that has been done is still used as a school learning in general, (2) Development of the Koran-based math learning through lesson plans, implementation and evaluation, (3) Development of math-based learning Qur'an impact more effective and increase students understanding of the mathematical relationship with the Qur'an. Koran- based learning can increase religious knowledge of learners and improve learning achievement.